PLAN ESTRATÉGICO PARA LA EMPRESA RADIAL SEMILLAS DE AMOR DE LA CIUDAD DE CATAMAYO - Lituma Saraguro, Olga Esther (2016)
This company is established in the year 2003 in the city of Catamayo made up of a family, the same who contributed capital to undertake the dream of the head of the family to create a radial radial company This company is a family business currently located in the city of Catamayo street Eugenio Espejo and October 9 by the Municipal Market dedicated to serving the community and own well The fundamental basis of all research is to develop flexible and achievable objectives therefore consider appropriate the following objectives: • Proposal of continuous improvement for the seeds of love within the city of Catamayo • Diagnosis of the administrative structure and relationships of the seeds of Love Radio. • Design the Organic Functional Manual • Design Procedures Manual • Designing the User Functions Internal analysis where reference was made to the history of the Seeds of Love 89.7Fm radio and the legal constitution of the same was made, the organization chart to check how it is organized hierarchically and staff that has been developed, also it studied the work tools to know what equipment the company has and if the current structure is adequate for normal operation of the different activities in this means of communication; the prices it charges for its services, where its relay with its signal and promotions that the radio uses the parameters are established will come: Mission, Vision, Goals, Policy and Survey, following the necessary methodology, proceeded to perform a SWOT analysis led to the Radio, to establish what the strengths, weaknesses, opportunities and threats are, for the purpose of strengthening or attack, as applicable, but not before performing a thorough analysis of the outcome of the polls whose deduction it provided the necessary to know that the company has significant market acceptance tools. RADIO SEMILLAS DE AMOR 89.7 Fm UNIVERSIDAD NACIONAL DE LOJA 7 Once detected the problem and established the causes and effects, it was to determine what would be the likely solution, leading to establish an array of strategies that will help correct difficulties or disadvantages and to strengthen opportunities and strengths. Likewise several factors that impede the smooth functioning of the same is detected, for it is proposed strategic goals, the same as if they are indeed a major breakthrough for the Company will be achieved by improving and achieving greater economic stability. After finishing with the Thesis Topic called: developing a strategic plan for the company RADIAL SEEDS OF LOVE ". Showed that: the radio company "SEEDS OF LOVE 89.7" Fm city of Catamayo is 3 years in the lojano market provides twenty four people working directly on this radio station, is supplied by local and provincial companies, Based on the object of study and after analyzing the business world think the main problem is: "THE EXISTENCE OF IMPROPER extructura DEVELOPMENT OF THIS COMPANY AND ABSENCE OF A PROPOSED development planning in terms of achieving proper positioning AND LEVELS OF EFFICIENCY AND EFFECTIVENESS OF THE RADIO STATION. Upon completion of the investigative work we can say that is fully compliant: The development of a strategic plan and diagnosis of the structure and management relations Radio seeds of love for the city of Catamayo allows the station to reach a competitive development and better profitability with their service. In the research work I have identified the key factors that allow the company to continue developing and likewise the factors that hinder their development. Strengths that possesses: It has entertainment programs, availability of financial resources, has a varied style of programming: News, Sport, Farándula; speaker voice coil, has a range of transmission.Local and Provincial level, good quality of service, good relationship with all members of the organization. RADIO SEMILLAS DE AMOR 89.7 Fm UNIVERSIDAD NACIONAL DE LOJA 8 The main opportunities: positive, favorable factors exploitable company that owns the radial enable competitive advantages. As is: Development of innovation in technology, Convention commercials with different companies within the town and outside, supporting the development of micro, excellent cultural level internet network new markets, population growth, displaying products in free trade. It has weaknesses: factors that cause a harmful position against the competition, lacking resources, such as activities and skills do not develop positively. As is the lack of advertising, lack of promoting the product, lack of staff training, little structural organization according to the needs. Threats have to face are different situations of the environment that adversely affect attacking the permanence of the company. As high tariffs to import computers, there is no HR department, difficulty generating from the information a democratic and civic political culture, closure of media, economic instability, a crisis of values imposed high, imposing new ones living laws. Seeds of Love Radio 89.7 Fm Radio seeds of love, is a radio station particular character, which encourages information from different schedules every day of every month. Geographic location The radio station is located in the Catamayo canton in the province of Loja in the streets Street Eugenio mirror and October 9, opposite the market